(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The treatment of textile azo dyes in wastewater has posed a significant challenge for decades due to their remarkable chemical, photolytic, and microbiological stability. This research focuses on developing a CuO–Fe2O4 nanocomposite, which provides an efficient method for converting visible light energy into the breakdown of -N=N- linkages found in azo dyes. This process not only mitigates the hazards associated with these materials but also facilitates the essential color removal required in wastewater treatment. To enhance the optical properties and increase the surface area of the CuO–Fe2O4 nanocomposite, the co-precipitation method was employed during its synthesis. The microstructure, crystallinity and morphology of the nanocomposite were characterized using X-ray diffraction (XRD), and scanning electron microscopy (SEM). A photocatalytic activity test was performed using methyl orange as a model azo dye. The results shows that the CuO–Fe2O4 composite exhibited excellent photocatalytic activity, achieving a degradation rate of up to 71.6%. In contrast, the degradation rates for CuO and -Fe2O3 were significantly lower, at 26.4% and 34.8% respectively. Kinetic study of the reaction revealed that the catalytic activity followed pseudo-first-order reaction model. These findings highlight the potential of the CuO–Fe2O4 nanocomposite as an effective solution for azo dye degradation in wastewater treatment. By leveraging its superior photocatalytic activity, this nanocomposite can significantly improve the efficiency of dye removal processes, making it a promising candidate for addressing the environmental challenges posed by textile wastewater.